A more complete picture of metal hyperaccumulation through next-generation sequencing technologies - Verbruggen, Nathalie; Hanikenne, Marc; Clemens, Stephan (Frontiers in Plant Science, 2013)
The mechanistic understanding of metal hyperaccumulation has benefitted immensely from the use of molecular genetics tools developed for Arabidopsis thaliana. The revolution in DNA sequencing will enable even greater strides in the near future, this time not restricted to the family Brassicaceae. Reference genomes are within reach for many ecologically interesting species including heterozygous outbreeders. They will allow deep RNA-seq transcriptome studies and the re-sequencing of contrasting individuals to unravel the genetic basis of phenotypic variation. Cell-type specific transcriptome analyses, which will be essential for the dissection of metal translocation pathways in hyperaccumulators, can be achieved through the combination of RNA-seq and translatome approaches. Affordable high-resolution genotyping of many individuals enables the elucidation of quantitative trait loci in intra- and interspecific crosses as well as through genome-wide association mapping across large panels of accessions. Furthermore, genome-wide scans have the power to detect loci under recent selection. Together these approaches will lead to a detailed understanding of the evolutionary path towards the emergence of hyperaccumulation traits.